Electrokinetic remediation technology for uranium contaminated soil: from fundamental principles to application challenges and breakthroughs - Bai, Yunlong; Zhang, Zhean; Jiang, Guoping; Niu, Siyuan; Peng, Zhiting; Liu, Longcheng (Frontiers in Chemical Engineering, 2025)
Uranium, extensively used in nuclear power generation, military applications, and scientific research, poses significant environmental and human health risks when released into soil due to its radiotoxicity and long half-life. Conventional remediation methods such as chemical leaching, stabilization, and bioremediation often face limitations including high costs, incomplete removal, prolonged treatment durations, and the potential for secondary pollution. In contrast, electrokinetic remediation (EKR) has emerged as a promising in situ technology for addressing uranium-contaminated soils, particularly in low-permeability environments where other methods are less effective. EKR operates by applying an external electric field across the soil matrix, inducing contaminant transport via mechanisms such as electromigration (ionic movement), electroosmosis (bulk fluid flow), and electrophoresis (movement of charged particles). These processes mobilize uranium species toward electrode zones, where they can be collected and removed through various treatment strategies. This review provides a comprehensive overview of recent advances in the application of EKR for uranium remediation, including fundamental transport mechanisms, system design parameters (e.g., electrode materials, electrolyte formulations, voltage gradients), and synergistic approaches such as coupling with phytoremediation and permeable reactive barriers. The role of numerical modeling in predicting system performance and optimizing operational parameters is also highlighted, along with the emerging potential of integrating renewable energy sources to enhance sustainability. Despite encouraging results at laboratory and pilot scales, challenges remain regarding scalability, energy efficiency, electrode longevity, and field deployment under heterogeneous site conditions. Future research should prioritize the development of hybrid systems, site-specific optimization strategies, and robust monitoring frameworks. Overall, EKR represents an environmentally friendly and technically viable solution for the remediation of uranium-contaminated soils, with considerable potential for application in nuclear facility decommissioning and long-term environmental restoration.